Late outcome after surgical and topical treatment for Aspergillus mediastinitis after heart transplantation. Issue 7 (21st April 2021) - Vogt, Paul R.; Aser, Raed; Schmidlin, Daniel; Mohacsi, Paul; Berdat, Pascal A.; Went, Phillip; Flepp, Markus; Mestres, Carlos A.
Abstract: The 7‐year long‐term survival after Aspergillus fumigatus mediastinitis after heart transplantation, an uncommonly described condition, is herein reported. A 66‐year‐old male developed an infection with A. fumigatus covering the entire thoracic cavity with a fungal turf after orthotopic heart transplantation. Repeated surgical removal of infectious and necrotic tissue together with innovative topical treatment using voriconazole and chlorhexidine combined with systemic antifungal treatment, helped in controlling the infection. Definitive wound closure was achieved by standard sternal refixation and latissimus dorsi muscle flap plasty. Survival after A. fumigatus mediastinitis after heart transplantation was achieved with sequential debridement in combination with topical application of antifungal agents.